2020
DOI: 10.3390/ijms21186708
|View full text |Cite
|
Sign up to set email alerts
|

Intra-Tumoral Angiogenesis Is Associated with Inflammation, Immune Reaction and Metastatic Recurrence in Breast Cancer

Abstract: Angiogenesis is one of the hallmarks of cancer. We hypothesized that intra-tumoral angiogenesis correlates with inflammation and metastasis in breast cancer patients. To test this hypothesis, we generated an angiogenesis pathway score using gene set variation analysis and analyzed the tumor transcriptome of 3999 breast cancer patients from The Cancer Genome Atlas Breast Cancer (TCGA-BRCA), Molecular Taxonomy of Breast Cancer International Consortium (METABRIC), GSE20194, GSE25066, GSE32646, and GSE2034 cohorts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
55
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(56 citation statements)
references
References 70 publications
(99 reference statements)
1
55
0
Order By: Relevance
“…In order to quantify the activity of the DNA repair pathway, we defined the DNA repair pathway score based on the gene set variation analysis (GSVA) score of the Molecular Signatures Database Hallmark DNA repair gene set ( Table S1 ), using the methodology we previously reported [ 4 , 5 , 9 , 10 , 11 ]. The DNA repair score correlated with expression of BRCA1 and BRCA2, arguably the most clinically significant DNA repair genes associated with cancer prognosis and treatment sensitivity ( Figure S1 ; Spearman’s rank correlation coefficient (r) = 0.576 ( p < 0.01) and 0.471 ( p < 0.01), respectively).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In order to quantify the activity of the DNA repair pathway, we defined the DNA repair pathway score based on the gene set variation analysis (GSVA) score of the Molecular Signatures Database Hallmark DNA repair gene set ( Table S1 ), using the methodology we previously reported [ 4 , 5 , 9 , 10 , 11 ]. The DNA repair score correlated with expression of BRCA1 and BRCA2, arguably the most clinically significant DNA repair genes associated with cancer prognosis and treatment sensitivity ( Figure S1 ; Spearman’s rank correlation coefficient (r) = 0.576 ( p < 0.01) and 0.471 ( p < 0.01), respectively).…”
Section: Resultsmentioning
confidence: 99%
“…The E2F target pathway score also demonstrated potential as a predictive biomarker for neoadjuvant therapy in breast cancer [ 10 ]. The angiogenesis pathway score revealed the association of intratumoral angiogenesis with inflammation, immune reaction, and metastatic recurrence in breast cancer [ 11 ]. These findings support the idea that pathway scores may be a useful tool in understanding the role of the DNA repair pathway in cancer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These tumors only grow to smaller lesions, which is correlated with the formation of fewer metastatic lesions [ 5 ]. Additionally, data show that tumors with a high angiogenesis score were associated with recurrent metastasis, especially to the brain and bone [ 178 ]. Additionally, DLL4 expression is increased in distant metastases compared to primary HNSCC tumors and associated with poor outcome [ 56 ].…”
Section: Notch Signaling In (Neo-)angiogenesismentioning
confidence: 99%
“…Analyses comparing molecular characteristics and the location of primary and recurrent tumors will elucidate the extent to which inflammation contributes to the regrowth of the primary tumor, disease recurrence, development of micrometastases, or the emergence of entirely new malignancies. Oshi et al demonstrated that intratumoral angiogenesis is associated with inflammation, immune reactions, and metastatic recurrence in breast cancer [ 53 ]. Although the direct correlation between inflammation in the primary tumor and cancer recurrence was not revealed, a relationship via angiogenesis may exist and have an important role in tumor recurrence.…”
Section: Types Of Cancermentioning
confidence: 99%